Silver–water nanofluid flow and convective heat transfer in a microfin tube equipped with loose-fit twisted tapes - Samruaisin, P.; Wongcharee, K.; Chuwattanakul, V.; Eiamsa-ard, S. (My University, 2020)
Heat transfer enhancement and performance of compact heat exchangers have been extensively studied in the past century for the purpose of promoting energy efficiency. Microfin tubes in single/two/multiple-phase flow heat exchangers into which twisted tape swirl generators are installed can promote heat transfer with a moderate pressure loss penalty. This article reports on the enhanced heat transfer of silver–water nanofluids in a microfin tube into which loose-fit twisted tapes are installed in a counter-flow arrangement. The experiments were carried out using nanofluids with various silver concentrations (0.007–0.03 vol%), loose-fit twisted tapes with clearance ratios (c/D) of 0.0 (tight-fit), 0.05, 0.075 and 0.1, for a twist ratio, y/W, of 2.0. The results indicate that the heat transfer rate (Nu) and pressure drop (f) increase with a decrease in clearance ratio (c/D) and increase in silver (Ag) nanoparticle concentration. Additionally, the thermal performance factor tends to increase with the decrease in Reynolds numbers.
Keywords: Friction factor; Heat transfer; Loose-fit twisted tapes; Microfin tube; Silver–water nanofluids; Thermal performance